2003
DOI: 10.1177/104973102237471
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Meditation Techniques on Psychosocial Functioning

Abstract: Objective: An experiment was conducted to determine the effects of chanting the maha mantra on stress, depression, and the three gunas—sattva (enlightenment), rajas (passion), and tamas (inertia)—described in the Vedas as the basis of human psychology. Primary hypotheses of the study were that the maha mantra group would increase sattva and decrease stress, depression, rajas, and tamas significantly more than the other groups. Method: Participants were tested at pretest, posttest, and follow-up, with testing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 24 publications
3
44
0
Order By: Relevance
“…Coleman and colleagues 13,36 found that prayer was used as a self-care strategy for managing HIV-related symptoms, including depression, fatigue, and nausea. Wolf and Abell 37 found that repetition of the mantra compared to a placebo mantra or notreatment control resulted in decreased depression and anxiety in adults.…”
Section: Kemppainen Et Almentioning
confidence: 99%
“…Coleman and colleagues 13,36 found that prayer was used as a self-care strategy for managing HIV-related symptoms, including depression, fatigue, and nausea. Wolf and Abell 37 found that repetition of the mantra compared to a placebo mantra or notreatment control resulted in decreased depression and anxiety in adults.…”
Section: Kemppainen Et Almentioning
confidence: 99%
“…Thus, these subscales are appropriately nonorthogonal. Wolf and Abell (2003) utilized the Vedic scale in an experiment with mantra chanting, a Vedic practice. Utilizing this traditional Eastern spiritual practice as an independent variable, they studied the effects of Hare Krishna mantra meditation on stress, depression, and the three Modes of Nature.…”
mentioning
confidence: 99%
“…While the evidence for its efficacy is preliminary and inconclusive at present, meditation’s possible benefits may include ameliorating depression, 9 improving anxiety, 10 promoting abstinence from drugs of abuse, 11,12 and reducing the self-injurious behaviors of personality disordered patients. 13 In this review, the available literature on the role of meditation in addressing psychiatric illness, and specifically substance use disorders, will be addressed.…”
mentioning
confidence: 99%